2022
DOI: 10.1186/s12889-022-14605-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the body composition of boys aged 11–18 years due to COVID-19 measures in the Czech Republic

Abstract: Background The lockdown measures related to coronavirus disease 2019 (COVID) impacted the health of adolescents by reducing physical activity (PA). The physical changes in response to decreases in PA can be measured with full body composition analysis. The aim of this study was to evaluate the effects of long-term PA restrictions on body fat (BF), fat-free mass (FFM) and skeletal muscle mass (SMM) in adolescents. Methods A total of 1669 boys (befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
2
0
2
Order By: Relevance
“…Kutac et al also reported the same results in boys in the Czech Republic. COVID-19 restrictions reduced physical activity, resulting in a significant increase in visceral fat volume and decrease in skeletal muscle mass (27). Although the present study did not analyze physical activity level, physical activity seems to have decreased due to a request to refrain from nonessential and non-urgent outings.…”
Section: Discussionmentioning
confidence: 59%
“…Kutac et al also reported the same results in boys in the Czech Republic. COVID-19 restrictions reduced physical activity, resulting in a significant increase in visceral fat volume and decrease in skeletal muscle mass (27). Although the present study did not analyze physical activity level, physical activity seems to have decreased due to a request to refrain from nonessential and non-urgent outings.…”
Section: Discussionmentioning
confidence: 59%
“…Ten představoval trend mírného snížení na úrovni jednoho procenta nebo tendenci ke stagnaci v relativním zastoupení tukové frakce u chlapců bez pravidelně řízené PA . Negativní vliv pandemických restriktivních opatření na zdravý růst a vývoj dospívajícího organismu a změny složení těla u českých chlapců rovněž potvrzuje aktuální domácí studie, která uvádí u třináctiletých a čtrnáctiletých chlapců zvýšení zastoupení tělesného tuku o hodnoty 4,8 % respektive 5,1 % (Kutáč et al, 2022). Nalezená zjištění zvýšení podílu tukové frakce na úrovni kolem pěti procent lze považovat i za věcně významná s ohledem na využití BIA analýzy a hodnoty přesahující interval definované střední chyby měření (Kutáč, 2015;Raven et al, 2013;Sigmund et al, 2015a).…”
Section: Diskuzeunclassified
“…A to z důvodu, že hodnoty v zastoupení kosterního svalstva u nesportujících chlapců kolem čtrnáctého roku se v období před pandemií ustalovaly na úrovni 42 % zastoupení svalstva v rámci složení těla . Kutáč et al (2022) dokonce uvádí snížení o 3,8 % v zastoupení kosterního svalstva u českých chlapců ve věku třináct a čtrnáct let s ohledem na období restriktivních protipandemických opatření. Nalezená zjištění pozitivního vývoje u hráčů RFA lze podpořit i změnami individuálních somatotypů a jejich posunu v rámci somatografu (Obrázek 2).…”
Section: Diskuzeunclassified
“…Relatively few studies have investigated how the COVID-19 pandemic has influenced body composition [ 14 – 16 ] or cardiometabolic markers [ 17 ] and these have mostly been performed in small, selected populations [ 14 – 16 ]. One study on 1 669 boys in Czechia [ 18 ] observed that skeletal muscle mass decreased after physical activity restrictions, although no difference was found in body mass. Another study found no changes in body composition in healthy women before and after COVID-19 lockdown in Spain [ 16 ].…”
Section: Introductionmentioning
confidence: 99%